BIOTECHNOLOGY OF TARO PRODUCTS THAT CONTAIN LOW GLYCEMIC INDEX TO BE SUBSTITUTE FOOD FOR PEOPLE WITH DIABETES - Adhika, Hanan Nur (Khazanah: Jurnal Mahasiswa, 2021)
Diabetes is a serious problem in Indonesia. Even people with diabetes increases every year. The latest data from the International Diabetes Federation (IDF) shows Indonesia is ranked seventh in the world with 10.7 million people with diabetes. This can be caused by consuming food without paying attention to the high glycemic index (GI) content in food ingredients. Therefore, foodstuffs containing a low glycemic index are needed and are usually found in tubers, especially taro. This study aims to determine the biotechnology of processed food from taro for diabetics. With the biotechnology of processed food products from taro, it helps diabetics to control their blood sugar. This research method is carried out by quantitative methods or based on previous research studies. Taro has a low glycemic index content so it can be consumed by diabetics. With a low GI content in taro it can control the increase of blood sugar levels. Taro can actually be processed into a more varied staple food. Taro can be made into cereals or flakes so it can make easier to consume. With biotechnology process of taro products, diabetics can more easily control blood sugar levels in the body because of its low glycemic index content. Keywords: Diabetes,taro,Glycemic.